Inland Waters - Inland Waters (Taylor & Francis, 2026)
Inland Waters is the peer-reviewed, scholarly outlet for original papers that advance science within the framework of the International Society of Limnology (SIL). The journal promotes understanding of inland aquatic ecosystems and their management. Subject matter parallels the content of SIL Congresses, and submissions based on presentations are encouraged.
FI 1
Q1
Keywords: Biological; Earth & Environmental Food Science; Limnología; Aguas continentales; Acuerdos transformativos; Transformative agreements; Ecosistemas acuáticos continentales; Gestión de ecosistemas